2023
DOI: 10.3390/molecules28052156
|View full text |Cite
|
Sign up to set email alerts
|

The Synergy between Zinc and Antimicrobial Peptides: An Insight into Unique Bioinorganic Interactions

Abstract: Antimicrobial peptides (AMPs) are essential components of innate immunity across all species. AMPs have become the focus of attention in recent years, as scientists are addressing antibiotic resistance, a public health crisis that has reached epidemic proportions. This family of peptides represents a promising alternative to current antibiotics due to their broad-spectrum antimicrobial activity and tendency to avoid resistance development. A subfamily of AMPs interacts with metal ions to potentiate antimicrobi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 93 publications
0
9
0
Order By: Relevance
“…It is commonly reported that peptide-zinc chelate can improve the bioavailability of intestinal zinc in the human body (Wang et al 2014 ). Similarly, previous studies have suggested that peptide-zinc chelates have strong anti-proliferative ability for pathogenic bacteria and simultaneously low toxicity for human body (Donaghy et al 2023 ). Despite many researches on the structure and intestinal absorption of peptide-zinc chelates, few studies were devoted to their antimicrobial activity and mechanism.…”
Section: Discussionmentioning
confidence: 70%
“…It is commonly reported that peptide-zinc chelate can improve the bioavailability of intestinal zinc in the human body (Wang et al 2014 ). Similarly, previous studies have suggested that peptide-zinc chelates have strong anti-proliferative ability for pathogenic bacteria and simultaneously low toxicity for human body (Donaghy et al 2023 ). Despite many researches on the structure and intestinal absorption of peptide-zinc chelates, few studies were devoted to their antimicrobial activity and mechanism.…”
Section: Discussionmentioning
confidence: 70%
“…In the title complex, the highly acidic hydrogen atom is released, allowing another N-H to form a hydrogen bond. In polyamine complexes such as Zn II -cyclen and Zn II -cyclam, the N-H group involved in ring formation can contribute to the hydrogen bonding network with counter anions and/or ligands (Ichimaru et al, 2021;Donaghy et al, 2023). In our previously reported complex of FU À bound to Zn II -cyclen, the carbonyl oxygen of FU À formed hydrogen bonds with the N-H of cyclen and a perchlorate ion (Ichimaru et al, 2023).…”
Section: Figurementioning
confidence: 80%
“…These cationic α-helix AMPs usually as stable or unstable pore formers. The unstable pores can generate a reorganization of the membrane surface and consequently reorient proteins and receptors, resulting in a change in the transmembrane potential, causing an imbalance and cell death ( Łoboda et al, 2018 ; Donaghy et al, 2023 ). However, just as helices can be formed and incorporated within the membrane to form pores, so can several different types of amphipathic structures be formed, not necessarily imposed by a strict primary or secondary structural organization ( Tossi et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, just as helices can be formed and incorporated within the membrane to form pores, so can several different types of amphipathic structures be formed, not necessarily imposed by a strict primary or secondary structural organization ( Tossi et al, 2000 ). As well as helical amphipathic, resulting in part from punctual interactions of the residues within a given sequence, other environmental factors such as pH conditions, ionic strength, and the presence of divalent cations are responsible for AMP activity effectiveness ( Donaghy et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%